Survival Strategies Adopted by Marginalized People in War Affected Regions: A Case Study of North Central Sri Lanka - Sangasumana, P. (My University, 2019)
Several thousand people had displaced in some “Conflict-locked” areas while a large number of human settlements have become vulnerable for the negative consequences of the prolonged armed conflict, particularly in the Northern and North Central Provinces of Sri Lanka. Hence, the human, social, and livelihood security issue of the families in these armed conflict induced areas of Sri Lanka had become a serious socio-political concern during the past three decades. Accordingly, the objective of this research paper was to examine the different vulnerabilities faced by communities as well as to measure the survival strategies adopted by them. The study area was the village of Yakawewa in Kebithigollewa Division of North Central Province of Sri Lanka. A large number of villagers from Yakawewa were killed and maimed by the roadside claymore attack of Tamil terrorists in 2006. This single event marked a turning point in the decade‟s long conflict of the country as it considered to have significantly swayed the government of Sri Lanka stance towards seeking a military solution to the conflict. The field work for this was done in 2010-2018 which used a rich array of qualitative techniques such as in-depth interviews and focus group discussions, particularly in a longitudinal manner. Research results revealed that multi-faceted coping strategies are being adopted by resettled Sinhalese in Yakawewa village in the phase of transforming from conflict-locked to a normal situation. The nature and sequence of their restoring process were depended on individuals‟ economic, social and political capabilities and attitudes. Household level coping strategies are strong in adapting to the new situation because in many cases individual rationality has come to the fore instead of collective rationality. In addition, many resettlement issues are being faced by the returnees as a result of emerging property issues, competition over the resources, physical and social isolation, subsistent attitudes and lack of self-esteem etc. It can be concluded that most of the survival strategies are onsite practices but preparedness mechanism.
Keywords: Displacement, Resettlement, Survival Strategies, Security, Vulnerability